2017
DOI: 10.3171/2016.8.spine16542
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique to correct kyphosis in cervical myelopathy due to continuous-type ossification of the posterior longitudinal ligament

Abstract: OBJECTIVE Although posterior decompressive surgery is widely used to treat patients with cervical myelopathy and multilevel ossification of the posterior longitudinal ligament (OPLL), a poor outcome is anticipated if the sagittal alignment is kyphotic (or K-line negative). Accordingly, it is mandatory to perform anterior decompression and fusion in patients with cervical kyphosis. However, it can be difficult to perform anterior surgery because of the high risk of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Moreover, some researchers have suggested that dynamic factors stimulate the progression of OPLL, and stabilization of the range of motion can reduce the progression of OPLL. [54][55][56][57][58][59] There are options for posterior decompression and fixation if it is difficult to directly remove OPLL by the anterior approach for any reason, especially when combined with kyphosis. Katsumi et al 59 evaluated whether laminoplasty with instrumented fusion (posterior decompression and fusion [PDF] group) suppresses the progression of OPLL in comparison with stand-alone laminoplasty (LP group), using their novel OPLL volume analysis with 3-dimensional CT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some researchers have suggested that dynamic factors stimulate the progression of OPLL, and stabilization of the range of motion can reduce the progression of OPLL. [54][55][56][57][58][59] There are options for posterior decompression and fixation if it is difficult to directly remove OPLL by the anterior approach for any reason, especially when combined with kyphosis. Katsumi et al 59 evaluated whether laminoplasty with instrumented fusion (posterior decompression and fusion [PDF] group) suppresses the progression of OPLL in comparison with stand-alone laminoplasty (LP group), using their novel OPLL volume analysis with 3-dimensional CT.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior decompression surgery can safely achieve the decompression of the spinal cord that results from extensive OPLL. However, there are limitations in posterior decompression surgery, it does not always produce the expected space for cases with a highly narrowed spinal canal or a bad lordosis [16,17]. Furthermore, the posterior decompression surgery is accused of higher incidence of C5 palsy, postoperative kyphotic change, and postoperative progression of the ossified OPLL lesion in many studies [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Then anterior surgery can be added priorly to correct the curvature. 51 The combined approach can be performed in one-stage or two-stages. Though it combines the advantages of direct and indirect decompressions, its high risk should be paid attention.…”
Section: Treatmentmentioning
confidence: 99%